Implementasi Media Kreatif Scrapbook untuk Pembelajaran Fikih yang Menyenangkan di Madrasah Ibtidaiyah - Latifah Latifah (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2023)
This study aims to develop scrapbook learning media to increase students' interest in learning fiqh at MI Al-Muttaqin. The problem faced is that fiqh learning tends to be boring because it uses more lecture methods, while students need interesting media to make it easier to understand fiqh material. This study uses the Research and Development (R&D) method which refers to the development steps of Borg & Gall. The study was conducted at MI Al-Muttaqin with the following results: first, the application of scrapbook learning media to fiqh subjects in grade III showed high student enthusiasm. Second, the development of this media was carried out through several development procedures with the results of the validity test showing very valid criteria, namely 96% for material validation and 84% for design validation. Third, there was a significant increase in student interest in learning, with an average value before using scrapbook media of 64.9% and increasing to 85.45% after using the media. This study concludes that the use of scrapbook media can increase students' interest and understanding of fiqh lessons.